2007
DOI: 10.1007/s10562-007-9133-6
|View full text |Cite
|
Sign up to set email alerts
|

Steam reforming of ethanol on Ni–CeO2–ZrO2 catalysts: Effect of doping with copper, cobalt and calcium

Abstract: Steam reforming (SR) and oxidative steam reforming (OSR) of ethanol were investigated over undoped and Cu, Co and Ca doped Ni/CeO 2 -ZrO 2 catalyst in the temperature range of 400-650°C. The nickel loading was kept fixed at 30 wt.% and the loading of Cu and Co was varied from 2 to 10 wt% whereas the Ca loading was varied from 5 to 15 wt.%. The catalysts were characterized by various techniques, such as surface area, temperature programmed reduction, X-Ray diffraction and H 2 chemisorption. For Cu and Co doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 53 publications
2
36
0
1
Order By: Relevance
“…Moreover, the high thermal stability of ceria is attractive for reactions which are conducted at high temperatures [2]. Therefore, ceria has been extensively utilized in three-way catalysts [5][6][7] and fuel cells [8,9], as well as investigated for its activity in catalytic reactions such as CO oxidation [10,11], steam reforming [12][13][14][15][16][17], and water gas shift (WGS) [18,19].…”
Section: +mentioning
confidence: 99%
“…Moreover, the high thermal stability of ceria is attractive for reactions which are conducted at high temperatures [2]. Therefore, ceria has been extensively utilized in three-way catalysts [5][6][7] and fuel cells [8,9], as well as investigated for its activity in catalytic reactions such as CO oxidation [10,11], steam reforming [12][13][14][15][16][17], and water gas shift (WGS) [18,19].…”
Section: +mentioning
confidence: 99%
“…Kelfin et al examined the influence of preparation methods on the behavior of Co-Ni/Al 2 O 3 catalysts in the steam reforming of propane [18]. However, there are only very limited investigations of the steam reforming of ethanol over Co-Ni bimetallic catalysts [16,19,20]. Besides working as catalysts, both Ni and Co have another interesting feature, functioning as an oxygen carrier facilitating chemical looping and autothermal reforming.…”
Section: Introductionmentioning
confidence: 99%
“…In several literature reports, it has been indicated that CeO 2 is a better support material for Ni than MgO, Al 2 O 3 , and TiO 2 in the reforming of oxygen-containing substances [15,16,27,30] For the reduction of carbon formation, the addition of a small amount of CeO 2 to Ni(5 wt%)/CaOZrO 2 catalyst was examined. Figure 7 shows the effects of different preparation methods for CeO 2 -loaded catalysts on the performance of the reforming of glycerin at 600°C.…”
Section: Effects Of Ceo 2 Addition On Catalyst Performancementioning
confidence: 99%
“…cations with one of these cations leads to a negative overall charge that is compensated for by an increased number of oxygen vacancies, in order to maintain electrical neutrality. Oxygen mobility is therefore enhanced, making it possible for stabilized ZrO 2 to be employed as a catalytic support in the reforming of hydrocarbons [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%